Optimasi Kinerja Wellstream Cooler Sebagai Sistem Pendinginan Gas Alam dari Sumuran terhadap Pengaruh Laju Alir dan Perbedaan Suhu Lingkungan di Platform PHE NSO Offshore - Teuku Tarich Akbar; Reza Fauzan; Alfian Putra (Politeknik Negeri Lhokseumawe, 2023)
This gas source that comes from the bowels of the earth contains many impurities and heavy hydrocarbons, both of which must be separated or even eliminated. To purify the treated gas to prevent damage to process equipment or pipe clogging. The removal process includes H2S removal, CO2 removal, oily water removal, mercury removal, and water content removal in natural gas. This study aims to determine the effect of flow rate and ambient temperature differences on the performance of the wellstream cooler and the level of efficiency of the heat transfer process in the wellstream cooler. Observations will be focused on the offshore platform wellstream cooler cooling system at PT. PHE NSO. Based on observational data, the results obtained using the Hysys method by entering the required data completely, Hysys will automatically perform calculations according to what is required and the calculation results will be plotted in graphical form. Heat transfer efficiency based on Hysys application calculations all show results of 99%. Thus it can be seen the effect of changes in flow rate and ambient temperature on the heat transfer process. The greater the flow rate, the greater the heat transfer that occurs and the higher the ambient temperature, the smaller the heat transfer occurs, so that the lower the ambient temperature, the more effective the heat transfer occurs.